Pemberontakan Petani Banten Tahun 1888 dalam Kitab Manhaj Al-Istiqamah Fi Ad-Din Bi As-Salamah Karya Sayyid Utsman Bin Yahya - Putri, Syifana A’Wuru; Najmul Umam, M Mutfi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The peasant rebellion in Banten occurred in 1888 criticized by Sayyid Utsman bin Yahya through his work entitled Manhaj al-Istiqa ̅mah fi ̅ ad-Di ̅n bi as-Sala ̅mah. This peasant rebellion was a social movement launched by religious leaders. The leaders echoed the ideology of jihad, a holy war movement to attack the power of the Dutch colonial government which was considered an infidel power, but according to Sayyid Utsman, this rebellion was not a jihad movement but a mistaken religious movement. This study aims to determine the views of Sayyid Utsman in his work entitled Manhaj al-Istiqa ̅mah fi ̅ ad-Di ̅n bi as-Sala ̅mah regarding the peasant rebellion in Banten in 1888 AD. The method used is the historical method, namely; heuristics, criticism, interpretation, and historiography using the study of the theory of jihad 'Abd al-Samad al-Falimbani through his work entitled Nasihat al-Muslimin wa Tadzkirat al-Mu'minin fii Fada'il al-Jihad fi Sabil Allah wa Karamat al-Mujahidin fii Sabil Allah. This method was chosen to trace the life of Sayyid Utsman and the Banten peasant rebellion from a historical perspective. In this study the author found several results that had been traced, namely; regarding the manuscript of Sayyid Utsman Manhaj al-Istiqa ̅mah fi ̅ ad-Di ̅n bi as-Sala ̅mah which condemned the rebellion in Cilegon Banten as a wrong movement, and discussed a lot about heresy that was still carried out by the Nusantara community and followers of the tarekat. Sayyid Utsman was a scholar of fiqh, his works which were considered pro-Dutch became polemic. In addition, Sayyid Utsman's closeness to the Dutch made Sayyid Utsman receive many awards.